Media Literacy Strategy for Youth Generation Based on Segmentation in Jakarta using the AHP Model and K-Means Clustering - Hardy R Hermawan; Hermanto Siregar; Patria Laksamana (Institute of Research and Community Outreach - Petra Christian University, 2026)
The high digital penetration in Jakarta has not been matched by adequate media literacy, particularly among the younger generation. This study proposes an integrative model combining the Analytical Hierarchy Process (AHP) and K-Means Clustering to design a data-driven and behaviorally segmented media literacy strategy. Data were collected through in-depth interviews with 15 practitioners and experts, as well as a survey of 202 young respondents aged 15–24 from five regions of Jakarta. The AHP approach was used to identify priority dimensions of media literacy, encompassing cognitive, technical, ethical, and participatory aspects. K-Means clustering was employed to group individuals based on their digital competency characteristics and to empirically map literacy segmentation patterns. The results reveal three main clusters with significant differences in media usage patterns, ethical awareness, and critical capacities. These findings confirm the importance of adaptive and evidence-based media literacy strategies, rather than merely normative interventions. This integrative model is expected to form the basis for policymaking and the design of media literacy programs in Indonesian urban areas.